(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article investigates the methods and challenges involved in presenting behavioral verbs in Uzbek-English dictionaries. By analyzing several authoritative dictionaries, it discusses inconsistencies in equivalence, the influence of cultural nuances, and lexicographic techniques used for semantic clarification. The study highlights the need for comprehensive, context-rich entries to better serve diverse dictionary users, from language learners to professional translators.Behavioral verbs, which denote habitual actions, mannerisms, and characteristic behaviors, are essential components of both Uzbek and English vocabularies.